2017
DOI: 10.1002/etc.3810
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric chlorinated polyfluorinated ether sulfonate and ionic perfluoroalkyl acids in 2006 to 2014 in Dalian, China

Abstract: Chlorinated polyfluorinated ether sulfonate (Cl-PFESA; trade name F-53B) is an alternative product for perfluorooctane sulfonate (PFOS) used in metal plating; little is known about its levels in the environment and its risks. To our knowledge, the present study constitutes the first report of Cl-PFESA in the atmosphere. In 2006 to 2014, C8 Cl-PFESA, along with ionic perfluoroalkyl acids (PFAAs), was detected in atmospheric particulate matter in Dalian, China. Concentrations of C8 Cl-PFESA increased from 140 pg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…In short, the mean values of method quantification limits (MQLs) ranged from 0.022 ± 0.010 pg/m 3 (perfluorohexane sulfonic acid, PFHxS) to 0.923 ± 0.424 pg/m 3 (perfluoropentanoic acid) (Supporting Information, Table S6). The MQLs in this study were comparable to those reported by Müller et al (0.09–1.06 pg/m 3 ) and Liu et al (0.31 and 0.62 pg/m 3 ) using large-volume sampling devices but higher than those collected by an annular denuder with a filter pack system (0.002–0.044 pg/m 3 ) . The corresponding procedural recovery ( n = 14) for spiked PFAS ranged from 74 to 95% and from 65 to 86% in 25 and 47 mm QFFs, respectively.…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…In short, the mean values of method quantification limits (MQLs) ranged from 0.022 ± 0.010 pg/m 3 (perfluorohexane sulfonic acid, PFHxS) to 0.923 ± 0.424 pg/m 3 (perfluoropentanoic acid) (Supporting Information, Table S6). The MQLs in this study were comparable to those reported by Müller et al (0.09–1.06 pg/m 3 ) and Liu et al (0.31 and 0.62 pg/m 3 ) using large-volume sampling devices but higher than those collected by an annular denuder with a filter pack system (0.002–0.044 pg/m 3 ) . The corresponding procedural recovery ( n = 14) for spiked PFAS ranged from 74 to 95% and from 65 to 86% in 25 and 47 mm QFFs, respectively.…”
Section: Methodssupporting
confidence: 85%
“…However, current knowledge of its atmospheric levels and transport is very limited. It was first reported in the atmospheric PM collected from Dalian, China, with concentrations in the range of 85.9–722 pg/m 3 . Another study reported 6:2 Cl-PFESA in the atmospheric PM of the Bohai Sea with concentrations ranging from <0.04 to 3.9 pg/m 3 (mean concentration: 1.6 ± 1.2 pg/m 3 ) .…”
Section: Resultsmentioning
confidence: 93%
“…As the major ingredient of F-53B used for metal plating industries, Cl-6:2 PFESA was detected to have a low contribution of 2% ± 1% of ∑PFASs, which was lower than PFOS (8% ± 3%). Liu et al (2017) reported a larger contribution of Cl-6:2 PFESA (37-95%) than PFOS in Dalian, China, which had a converse composition pattern. The degradation of Cl-6:2 PFESA to hydrogen-substituted PFESAs has been reported in anaerobic conditions (Lin et al, 2017).…”
Section: Concentrations Composition and Sources Of Pfass In Airmentioning
confidence: 92%
“…The occurrence of 6:2 Cl-PFESA was first reported in chrome-plating wastewater in 2013 . Since then, it has been detected in drinking water, surface water, electroplating wastewater, sludge, and the atmosphere at comparable or higher concentrations than PFOS in China. Given its similar structure, larger molecular size, and higher octanol–water partition coefficient ( K ow ) value than PFOS (6:2 Cl-PFESA: 5.42, PFOS: 4.49, derived using EPIWEB 4.1), the bioaccumulative potential of 6:2 Cl-PFESA is estimated to be even higher than that of PFOS. , As reported in Shi et al, the median whole-body bioaccumulation factor (BAF whole body ) of 6:2 Cl-PFESA in crucian carp ( Carassius carassius ) is significantly higher than that of PFOS (i.e., 4.12–4.32 and 3.43–3.28, respectively). In addition, according to Appendix XIII of the REACH Code, 6:2 Cl-PFESA is a strong bioaccumulative organic pollutant .…”
Section: Introductionmentioning
confidence: 99%